Hypokalemia: a clinical update - Kardalas, Efstratios; Paschou, Stavroula A; Anagnostis, Panagiotis; Muscogiuri, Giovanna; Siasos, Gerasimos; Vryonidou, Andromachi (Endocrine Connections, 2018)
Hypokalemia is a common electrolyte disturbance, especially in hospitalized patients. It can have various causes, including endocrine ones. Sometimes, hypokalemia requires urgent medical attention. The aim of this review is to present updated information regarding: (1) the definition and prevalence of hypokalemia, (2) the physiology of potassium homeostasis, (3) the various causes leading to hypokalemia, (4) the diagnostic steps for the assessment of hypokalemia and (5) the appropriate treatment of hypokalemia depending on the cause. Practical algorithms for the optimal diagnostic, treatment and follow-up strategy are presented, while an individualized approach is emphasized.